IN VIVO MULTISTEP MUTAGENESIS INDUCTION USING COLCHICINE ON COWPEA MUTANT 1 (Vigna unguiculata L. Walp) - I Gede Ketut Susrama; I Gede Putu Wirawan (International Journal of Biosciences and Biotechnology, 2018)
In the previous research, we obtained three catagories of M1 mutant cowpea namely 1) purple pod mutant cowpea, 2) green pod mutant cowpea which has three pods in a stalk, and 3) green pod mutant cowpea which has two pods in a stalk. All those three catagories of M1 mutant cowpeas were treated again with colchicine in a multistep mutagenesis proses in vivo. Then, we found changes in number of leaflet in a petiole to 4 leaflets (quadrifoliate) and to five leaflets in a petiole (pentafoliate). These changes are indications that beside as a chromosome multipying alkaloid, colchicine causes other genetic changes as well. Through this mutagenesis research, we created gigas mutant cowpea that having longer leaves, longer pods and heavier seeds. The accurrence of two kinds of insect pests attack were found namely cowpea aphid Aphis craccivora and pod sucking bug Riptortus linearis.